2016
DOI: 10.1186/s12906-016-1306-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new simple scale to measure symptoms in heart failure from traditional Chinese medicine view: a cross-sectional questionnaire study

Abstract: Background: Current clinical practices used to functionally classify heart failure (HF) are time-consuming, expensive, or require complex calculations. This study aimed to design an inquiry list from the perspective of traditional Chinese medicine (TCM) that could be used in routine clinical practice to resolve these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…However, mean MLHFQ values available in the literature show a wide variation. According to Fu et al (2016) [47] and Mogle et al (2017) [48] who have validated the MLHFQ to Taiwan and Spanish populations, the mean MLHFQ score was 25.3 and 27.8 respectively. But a couple of studies have reported higher mean MLHFQ scores [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, mean MLHFQ values available in the literature show a wide variation. According to Fu et al (2016) [47] and Mogle et al (2017) [48] who have validated the MLHFQ to Taiwan and Spanish populations, the mean MLHFQ score was 25.3 and 27.8 respectively. But a couple of studies have reported higher mean MLHFQ scores [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth questionnaire was the Minnesota Living with Heart Failure Questionnaire (MLHFQ), which was used to assess the quality of life in patients with CHF and reliability was validated in Chinese [ 23 ]. It has 21 items, which comprise the physical dimension (8 items), emotional dimension (5 items), and additional dimension (8 items).…”
Section: Methodsmentioning
confidence: 99%
“…According to the clinical manifestations related to chronic heart failure, most scholars believe that heart failure belongs to the root deficiency and enrichment of symptoms. In recent years, many doctors [30] have supplemented the pathogenesis of chronic heart failure with their own clinical experience and classified chronic heart failure according to the different clinical manifestations of patients. In clinical practice, the results of association rules can be combined with the patient's symptoms to establish the syndrome type and conduct syndrome differentiation for treatment.…”
Section: Discussionmentioning
confidence: 99%